The influence of family character on the choice of foreign market entry mode: An analysis of Spanish hotel chains - Rosario Andreu; Diego Quer Ramón; Laura Rienda (European Research on Management and Business Economics (ERMBE), 2020)
Many studies have addressed how family character can influence the internationalisation process of family businesses. Nevertheless, the results obtained have not been conclusive. Depending on the perspective adopted, family businesses can be more or less averse to risk, more or less willing to relinquish their control, have a higher or lower limitation of resources, etc. Moreover, all these factors may influence the international strategies of family businesses. Drawing on the stewardship theory, this study analyses how family character affects the choice of foreign market entry modes by Spanish hotel chains.
Keywords: L83; M16; 650; Family business; Hotel sector; Internationalisation; Stewardship theory